Accounting students' perceptions of faculty evaluation process at UiTM Perlis / Rosiatimah Mohd Isa - Mohd Isa, Rosiatimah (Universiti Teknologi MARA, Perlis, 2011)
The primary purpose of this research is to survey accounting students' perceptions of faculty evaluation process. The study surveyed over 100 bachelors of accountancy students enrolled at UiTM Perlis in 2010. The study provides evidence that results of evaluations is perceived important and necessary to faculty members for formative purposes (improving in teaching performance and advancement) and not summative reason. More than fifty percent of the students wanted the results to be published. They felt that other methods of evaluations should be employed along with the students' evaluations. There are some elements of biasness in rating the faculty members by students namely, leniency and favorable personality.